2008
DOI: 10.1140/epjc/s10052-008-0739-7
|View full text |Cite
|
Sign up to set email alerts
|

Comment on the recent COMPASS data on the spin structure function g 1

Abstract: We examine the recent COMPASS data on the spin structure function g1 singlet. We show that it is rather difficult to use the data in the present form in order to draw conclusions on the initial parton densities. However, our tentative estimate is that the data better agree with positive rather than negative initial gluon densities.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…4, the results on g p 1 are presented. No significant dependence with the virtual photon energy is observed, in contrast with the prediction of a significant dependence of the singlet structure function g S 1 with ν predicted by the model of [7].…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…4, the results on g p 1 are presented. No significant dependence with the virtual photon energy is observed, in contrast with the prediction of a significant dependence of the singlet structure function g S 1 with ν predicted by the model of [7].…”
Section: Resultscontrasting
confidence: 93%
“…The same caveat applies to COMPASS, which can, nonetheless, reach even lower values of x, because of its particular trigger system [4] and of its much larger data set. On the other hand, theoretical models, still to be confronted with data, allow a smooth extrapolation to both the low Q 2 and the high Q 2 regions (using resummation, vector meson dominance) [5,6,7]. With the COMPASS data taken with a proton target, A d 1 and g p 1 can be measured at low x and low Q 2 with improved precision, complementing our measurement of A d 1 and g d 1 at low x and low Q 2 [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] we had shown that the arguments of Ref. [26] in favor of using the parametrization (48) in DGLAP can be used at large x only. Later, in Ref.…”
Section: Treatment Of αS At Large and Small Xmentioning
confidence: 97%
“…However, in fixed target experiments, x and Q 2 are highly correlated, and probing the low x region implies also entering the non-perturbative region of Q 2 < 1 (GeV/c) 2 , which is poorly known experimentally and where perturbative QCD cannot be applied. Nevertheless, this region allows studies of the transition from the non-perturbative regime of photoproduction to the perturbative region of deep inelastic scattering where several predictions were formulated [1,2,3]. Previously, the Spin Muon Collaboration (SMC) has presented its results on A p 1 and g p 1 in this region [4].…”
Section: Introductionmentioning
confidence: 99%